Ronin [videorecording (DVD)] - Frankenheimer, John, 1930-2002; Mancuso, Frank, Jr; Zeik, J. D. (John David); Mamet, David; De Niro, Robert; Reno, Jean, 1948-; McElhone, Natascha, 1969-; Skarsgård, Stellan; Bean, Sean; Pryce, Jonathan; Sudduth, Skipp; Lonsdale, Michaël, 1931-2020- (Metro Goldwyn Mayer Home Entertainment, 1999)
A group of freelance intelligence agents work together to steal a mysterious package, only to have a doublecross throw things into confusion.